Effects of Morbid Obesity and Metabolic Syndrome on the Composition of Circulating Immune Subsets - Wijngaarden, Leontine H.; van der Harst, Erwin; Klaassen, René A.; Dunkelgrun, Martin; Kuijper, T Martijn; Klepper, Mariska; Ambagtsheer, Gisela; IJzermans, Jan N. M.; de Bruin, Ron W. F.; Litjens, Nicolle H. R. (Frontiers in Immunology, 2021)
Morbid obesity is characterized by chronic, low-grade inflammation, which is associated with ‘inflamm-aging’. The presence of metabolic syndrome (MetS) might accelerate this phenomenon of metaflammation. In this study, we assessed the effects of morbid obesity and MetS on the composition of a broad spectrum of immune cells present within the circulation. A total of 117 morbidly obese patients (MOP) without MetS (MetS-), 127 MOP with MetS (MetS+) and 55 lean controls (LC) were included in this study. Absolute numbers of T cell, B cell, NK cell and monocyte subsets were assessed within peripheral blood using flow cytometry. Both absolute cell numbers and proportion of cells were evaluated correcting for covariates age, body mass index and cytomegalovirus serostatus. Although the absolute number of circulating CD4+ T cells was increased in the MetS+ group, the CD4+ T cell composition was not influenced by MetS. The CD8+ T cell and B cell compartment contained more differentiated cells in the MOP, but was not affected by MetS. Even though the absolute numbers of NK cells and monocytes were increased in the MOP as compared to LC, there was no difference in proportions of NK and monocyte subsets between the three study groups. In conclusion, although absolute numbers of CD4+ and CD8+ T cells, B cells, NK cells and monocytes are increased in MOP, obesity-induced effects of the composition of the immune system are confined to a more differentiated phenotype of CD8+ T cells and B cells. These results were not affected by MetS.